What are the solutions of the equation x4 – 5x2 – 14 = 0? Use factoring to solve.

Answers

Answer 1
Answer: We will use factoring:x^(4) -5 x^(2) -14 = 0 \n  x^(4) -7 x^(2) +2 x^(2) -14 =0 \n  x^(2) ( x^(2) -7)+2( x^(2) -7)=0  \n  ( x^(2) -7)( x^(2) +2)=0
x² - 7 = 0
x² = 7
x = √(7)
or x=-√(7)
x² + 2 = 0
x² = - 2, this part of equation has no solutions.
Answer 2
Answer:

Answer:

d on edge.

Step-by-step explanation:


Related Questions

If a caterer charges a fixed cost for preparing a dinner plus an additional cost for each person served. You know that the cost for 100 students will be $750 and the cost for 150 students will be $1050. find the caterers fixed cost and the cost per student served.
What percentage of Tommy's coins are dimes? Solving way please. Thank you.
When you use the distance formula, you are calculating the length of the (fill in blank) of a right triangle
Use the given graph to determine the limit, if it exists. A coordinate graph is shown with a horizontal line crossing the y axis at three that ends at the open point 2, 3, a closed point at 2, 1, and another horizontal line starting at the open point 2, -2. Find limit as x approaches two from the left of f of x. and limit as x approaches two from the right of f of x..
Add the decimals 64.5 +2.407+ 10+12.95

How would you convert 5 feet 6 inches to inches

Answers

66 inches. Since 1 foot is equal to 12 inches, all you need to do is to multiply 5 with 12. The answer will be 60. Since 6 inches are already given for the answer, just add up 60 with 6 for you to get 66 inches which is equivalent to 5 feet 6 inches.

Converting  5 feet 6 inches to inches is: 66 inches.

Here, we have,

given that,

convert 5 feet 6 inches to inches

we know that,

Since 1 foot is equal to 12 inches,

all we need to do is to multiply 5 with 12.

i.e. 5 * 12  = 60

The answer will be 60.

Since 6 inches are already given for the answer,

just add up 60 with 6

i.e. 60+ 6 = 66

for we to get 66 inches

which is equivalent to 5 feet 6 inches.

Learn more about the unit conversion here:

brainly.com/question/14350438

#SPJ6

What is the equation of the line that passes through the point (-3, 0) and has a slope of -1/3?​

Answers

Answer:

Y=-1/3x-1

Step-by-step explanation:

Y-0=-1/3(x+3)

The orbital period, P, of a planet and the planet’s distance from the sun, a, in astronomical units is related by the formula P = a Superscript three-halves. If Saturn’s orbital period is 29.5 years, what is its distance from the sun?

Answers

Answer:

9.54731702 astronomical units

Step-by-step explanation:

P=a^{(3)/(2) }

Substitute this value in the equation above:

29.5=a^{(3)/(2) }

(29.5)^{(3)/(2) } =a

a=9.54731702astronomicalunits

Hence, its distance from the sun is 9.54731702 astronomical units.

Answer:

its a

Step-by-step explanation:

on edge 2022

The sum of the roots of the equation (1/2)x^2-(5/4)x-3=0

a.5/2
b.2
c.1/2

Answers

(1/2)x² - (5/4)x - 3 = 0

0.5x² - 1.25x - 3 = 0

Comparing to the quadratic function, ax² + bx + c = 0,    
a = 0.5,  b = -1.2,  c = -3.

Sum of roots = -b/a   =    -(-1.25)/0.5 =    1.25/0.5 = 2.5

2.5 = 5/2  Option (a)
A)5/2 is the answer.

10. This model shows the area of a garden. Write two expressions thatrepresent the area.
Х
х
х
Х
х
1
1
1
1
1 1 1
1 1 1 1
1

Answers

Answer:

xxxxxxxx

111111

Step-by-step explanation:

Sorry & I really sorry

Answer:

Dont know how to explain

Step-by-step explanation:

Which set of ordered pairs does not represent a function?O{(-2,5), (0, -9), (8,-2), (7,4)}
O{(-3,4), (-5,4), (7, -3), (2, -9)}
O {(2, -9), (-5, -1), (-6, -3), (-5,7)}
O {(1, -8), (-9,-2), (-4,0), (4, -8)}

Answers

Step-by-step explanation:

{(2, -9), (-5, -1), (-6, -3), (-5,7)}

-5 appears twice ( this is not allowed for the function)